Pengaruh Beban Kerja Berlebih Dan Konflik Kerja Terhadap Kesehatan Mental Karyawan - Alicia Puteri Herdiany; Kokom Komariah; Faizal Mulia Z (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The research was aimed at determining the amount of the influence of Excessive Workload and Workplace Conflict towards Employee Mental Health at the Trading Company (PD) of Alam Aneka Aroma in Sukabumi City. Respondents in the research were amounted to 40 employees of PD. Alam Aneka Aroma. The research method used was quantitative method with descriptive and associative approaches. Conducted in the research were Normality Test, simultaneous statistical test (F Test), and partial statistical test (T Test). The result of the research show that there is a simultaneously positive influence between Excessive Workload and Workplace Conflict towards Employee Mental Health namely by 486.142 > 3.245, indicating that the value of F-Count is larger than F-Table. Meanwhile, partially, Excessive Workload has a positive and significant influence towards Employee Mental Health as proven by the value acquired from T-Count of 3.162, larger than that of T Table, which is 2.026, with significance level of 0.003 < 0.05. in addition, Workplace Conflict possesses a positive and significant influence towards Employee Mental Health as proven by the value obtained from the result of T-Count, which is 9.230, larger than that of the T-Table which is 2.026, with significance level of 0.000 < 0.05. Keywords : Excessive Workload, Workplace Conflict, Employee Mental Health